Assessment of Antibiotic Sensitivity Pattern of Bacterial Isolates in the Intensive Care Unit of a Tertiary Care Hospital in Eastern India - Pattanayak, Chaitali; Patanaik, Sunil K.; Datta, Pratyay Pratim; Panda, Parbaty (Issues and Developments in Medicine and Medical Research Vol. 10, 2022)
Background: Nosocomial infections are one of the leading causes of morbidity and mortality in hospitalised patients, particularly critically ill patients in the intensive care unit (ICU), where a large number of drugs are administered to the patient, resulting in the development of antibiotic-resistant pathogens. Objectives: The study was conducted to identify the prevalence of predominant bacterial microorganisms and their drug sensitivity and resistance in the ICU of a teaching hospital in Eastern India. Methods: From November 2011 to October 2012, a retrospective record-based study was performed in the ICU of Hi- Tech Medical College and Hospital in Odisha, Eastern India. The study included patients who were clinically suspected of having acquired any infection within 48 hours of being admitted to the ICUs. Clinically suspected laboratory samples were collected from patients and tested for antibiotic sensitivity. Results: Nosocomial infection occurred at a rate of 28.2 percent. The most common infection was urinary tract infection (54.9 percent). The most common isolate was E. coli (52.7%), followed by P. mirabilis (15.4%) and Ps aeruginosa (13.2 percent). Polymyxin B, Gatifloxacin, and Ceftriaxone were highly effective against E. coli, but it was highly resistant to Cephalexin, Cefadroxil, Tobramycin, and Prulifloxacin. Conclusions: The majority of the bacterial isolates tested positive for resistance to third generation cephalosporins and aminoglycosides. Regular surveillance of antibiotic susceptibility patterns, as well as judicious antibiotic use, are critical for lowering nosocomial infection rates and antimicrobial resistance.